2020
DOI: 10.3389/fmicb.2020.01712
|View full text |Cite
|
Sign up to set email alerts
|

A Newly Isolated Streptomyces sp. YYS-7 With a Broad-Spectrum Antifungal Activity Improves the Banana Plant Resistance to Fusarium oxysporum f. sp. cubense Tropical Race 4

Abstract: Fusarium wilt of banana caused by Fusarium oxysporum f. sp. cubense (Foc) is one of the most destructive diseases, severely limiting the development of banana industry. Especially, Foc tropical race 4 (Foc TR4) can infect and destroy almost all banana cultivars. Until now, there is still a lack of an effective method for controlling fusarium wilt. A biocontrol strategy using Actinobacteria is considered as a promising method for management of disease and pest. In this study, 229 Actinobacteria were isolated fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 70 publications
2
59
0
Order By: Relevance
“…The morphological characteristics of Foc TR4 mycelia treated with H3-2 extracts were assessed by scanning electron microscopy (SEM; TM4000Plus, Hitachi, Japan). The methods of sample preparation and analysis were referred to the publication with a slight modification ( Wei et al, 2020 ). A 5-mm-diameter disk of Foc TR4 was inoculated in the PDA plate containing 4 × EC 50 of strain H3-2 extracts.…”
Section: Methodsmentioning
confidence: 99%
“…The morphological characteristics of Foc TR4 mycelia treated with H3-2 extracts were assessed by scanning electron microscopy (SEM; TM4000Plus, Hitachi, Japan). The methods of sample preparation and analysis were referred to the publication with a slight modification ( Wei et al, 2020 ). A 5-mm-diameter disk of Foc TR4 was inoculated in the PDA plate containing 4 × EC 50 of strain H3-2 extracts.…”
Section: Methodsmentioning
confidence: 99%
“…Banana is an important food crop in the tropics and subtropics, and fusarium wilt is one of the most destructive diseases affecting agricultural production of this fruit. Biological control is a promising strategy for combating fusarium wilt, due to the advantages of high efficiency, broad spectrum, and the fact that it is relatively environmentally friendly ( Zhou et al, 2013 ; Wei et al, 2020 ). Previous studies have indicated that specific microbial groups, such as Pseudomonas , Streptomyces , Flavobacterium , etc., are closely related to plant disease suppression ( Mendes et al, 2011 ; Cha et al, 2016 ; Kwak et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…We did not find swollen mycelia in Foc TR4 treated with strain JBS5-6 extracts. This might be because the swollen morphology was an earlier symptom of abnormalities ( Wei et al, 2020 ). The antifungal ability of Streptomyces might be related to antibiosis, nutrient competition, degradative enzyme biosynthesis, nitrous oxide production, and quorum quenching ( Cohen and Mazzola, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the latest research trends have focused on developing new screening technologies for efficient dereplication and investigating rare samples from extreme and unexplored environments where microorganisms may have unique characteristics compared with those of known species and thus might produce novel bioactive secondary metabolites ( Suzuki, 2001 ). Extreme and unexplored environments include marine environments ( Yang et al, 2020 ), mountains ( Wei et al, 2020 ), deserts ( Sivakala et al, 2021 ), and rainforests ( Schneider et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%